INTEGRATING MOBILE LISTENING AND PHYSICAL ACTIVITY TO FACILITATE INTENTIONAL AND INCIDENTAL VOCABULARY ACQUISITION - Tetiana Zubenko; Allan Shwedel (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2019)
This paper examines the development and effectiveness of a strategy that promotes rapid vocabulary retention among university students who are learning English as a second language. This approach to vocabulary acquisition is based on research that shows that activating implicit memory has a stronger effect than simply activating intentional memory. The hypothesis was that listening to carefully structured mobile English vocabulary lessons during routine physical activity would have a significant and positive effect on students' vocabulary acquisition and performance. The audio lessons were designed to introduce vocabulary by moving from L1 to L2. Participants (N = 51) were first-year Ukrainian university students majoring in English as a second language. Their average age was 17-18. They were randomly assigned to one of three classes, one experimental and two comparison. The experimental group used the "integrating physical activity with listening to vocabulary lessons" strategy in addition to the traditional intentional learning strategy used by the comparison group. The results indicate that performance on the End-of-Unit test benefitted students who were in the Listening While Physically Active group. Their mean score was 81.9 versus 63.2 for the Comparison group. Results from a one-way ANOVA indicate that exam performance difference was statistically significant, F= 8.761, df = 1 , p < 05. Mobile devices offer students multiple opportunities to listen to, and pronounce, new vocabulary based on  L1 to L2 translation while performing routine physical actions. This allows students to create not only receptive but also reproductive skills of L2 translation and communication